Resources and The Style of Ibnabi Al-Suror Al-Bakri (D. 1087 AH) In His Book Nozhat Al-Absar wa Jahainat Al-Akhbar - Muhammad Zaky, Salleh; Abdul Hamid, Faisal @ Ahamad Faisal (Journal Al-Muqaddimah, 2017)
This research deals with an important subject, which is based on the explanation of the resources on which IbnAbi Al-Suror Al-Bakri (1087 AH) based his book â€œNozhat Al-AbsarwaJahainat Al-Akhbarâ€ on it. A book in the field of history that has exceptional importance, methodology and order. In which the author was able to combine between the historical periods, information and details in a single scientific vessel. The importance of this research is to shed light on the nature, diversity and importance of the sources on which IbnAbi Al-Suror Al-Bakri built this book on, and how he was able to formulate a method and methodology of his own based on the narration of historical information and analysis with the introduction of his own vision in his style and methodology. The question that the research seeks to answer is: how important the scientific sources and the nature and quality of these sources on which Al-Bakri used in the formulation of this important historical book, and whether the approach and style Al-Bakri used was exceptional in writing and studying the history. The research also seeks to find out the compatibility of Al-Bakri’s style in his book "Nozhat Al-AbsarwaJahainat Al-Akhbar " with the rest of the historians who have witnessed it, and whether he managed to find his own style by using the literary and scientific means that enabled him to be distinguished among the historians of his time.